New improvements in increasing trends of caesarean section: to compare the effectiveness of two techniques Misgav Ladach with Joel Cohen incision versus Munro Kerr with pfannenstiel incision for caesarean section - Sharma, Kanchan; Mani, Ankita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Caesarean section (C-section) is the most common surgery among women worldwide, and the global rate of this surgical procedure has been continuously rising. Hence, it is significantly crucial to develop and apply highly effective and safe caesarean section techniques. In this study, we aimed at assessing the safety and effectiveness of the Joel-Cohen-based Misgav Ladach technique and comparing the results with the transverse Pfannenstiel incision (Munro Kerr) for C-section. Methods: It was a prospective randomised controlled trial conducted on 100 women undergoing caesarean section at Patna Medical College and hospital in 2017. Patients were randomly allocated in 2 groups and intra operative and postoperative findings (blood loss, duration of surgery, post op fever, wound complication, APGAR scores etc. were calculated. Results: The duration of surgery was significantly low in Misgav Ladach technique (19.9 minutes vs. 29.54 minutes p value <0.001) Misgav technique was found economically better method as only 1 suture was used in 43 patients (p value<0.001). Post operative recovery (ambulation and bowel transit time) was found much early in Misgav Ladach vs. Munro Kerr (p value <0.001).Post operative use of analgesics was significantly less in Misgav technique (p value <0.0001). However no significant difference was observed in incidence of postoperative fever, blood loss and mean APGAR scoring of neonates. Conclusions: From this study it can be concluded that Misgav ladach method of caesarean section is associated with better short time post operative outcomes, especially resulting in reduction of pain and postoperative hospital stay.